Market platforms, industrial clusters and small business dynamics specialized markets in China - Ke, Ding.; Institute of Developing Economies (IDE), JETRO; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2012)
Specialized markets are a unique product of China's economic transition. They are marketplaces located in industrial clusters, specializing in the wholesale of local commodities and related goods. Ding Ke reveals that, despite their seemingly primitive form, specialized markets appeared in many of the modern industrial sectors and were paradoxically upgraded and expanded as these clusters developed. He argues that specialized markets have also formed solid linkages with marketplaces in various cities in China and in other developing economies. A powerful, emerging market-oriented distribution system has thus appeared. Based on thorough fieldwork covering ten years, and using the novel theory of the platform, this book clarifies the unique development logic of specialized markets.
1. Specialized markets and small business dynamics in China -- 2. Analytical framework -- 3. The general situation in the province of markets -- 4. Local government and platform governance in Yiwu -- 5. The specialized market system in the daily necessities industry : an observation from Yiwu market -- 6. Overseas linkages of specialized markets -- 7. Producer-distributor relationships in Yiwu market -- 8. Local government and inter-platform competition -- 9. The logic of quantitative expansion and qualitative upgrading in the market platform mode cluster -- 10. The typology of apparel clusters in China -- 11. Conclusion.
Includes bibliographical references and index.
Keywords: Markets -- China; Industries -- China; Small business -- China; Electronic books